2022
DOI: 10.3389/fphys.2022.1054773
|View full text |Cite
|
Sign up to set email alerts
|

New insights for the regulatory feedback loop between type 1 crustacean female sex hormone (CFSH-1) and insulin-like androgenic gland hormone (IAG) in the Chinese mitten crab (Eriocheir sinensis)

Abstract: To clarify the hormone control on sex determination and differentiation, we studied the Chinese mitten crab, Eriocheir sinensis (Henri Milne Edwards, 1854), a species with importantly economic and ecological significance. The crustacean female sex hormone (CFSH) and the insulin-like androgenic gland hormone (IAG) have been found to be related to the sex determination and/or differentiation. CFSH-1 of E. sinensis (EsCFSH-1) encoded a 227 amino-acid protein including a signal peptide, a CFSH-precursor-related pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…Previous studies have shown that Lvit-IAG1 and Lvit-IAG2 co-regulate the development of male external phenotypes and spermatogenesis in PSH shrimps, L. vittata [11]. As IAG is regulated by type I CFSH through a negative feedback loop in both dioecious and hermaphrodite crustaceans [10,23], male sexual differentiation is also negatively regulated by CFSH1b in L. vittata [10]. The present results demonstrate that Lvit-IL-17R negatively regulates male sexual differentiation in this species.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Previous studies have shown that Lvit-IAG1 and Lvit-IAG2 co-regulate the development of male external phenotypes and spermatogenesis in PSH shrimps, L. vittata [11]. As IAG is regulated by type I CFSH through a negative feedback loop in both dioecious and hermaphrodite crustaceans [10,23], male sexual differentiation is also negatively regulated by CFSH1b in L. vittata [10]. The present results demonstrate that Lvit-IL-17R negatively regulates male sexual differentiation in this species.…”
Section: Discussionsupporting
confidence: 67%
“…In both dioecious and hermaphrodite crustaceans, IAG and CFSH play pivotal roles in sexual differentiation [9][10][11]22,23]. IAG receptors have been identified in several crustacean species [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrity of the RNA was determined with the Agilent 2100 Bioanalyzer (Agilent Technologies, United States). Besides, chimeric crabs, collected in local crab farms, are genetically females whereas exhibit male characteristics such as AG and male gonopods (Zhu et al, 2022).…”
Section: Crab Sample and Rna Preparationmentioning
confidence: 99%
“…After 24 h, mature crabs were sampled for qRT-PCR, including the eyestalk ganglion and ovary in females and testis and AG in male crabs. To analyze the molecular function of dsRNA EsFem-1c, IAG (GenBank ID: KU724192.1) and crustacean female sex hormone 1 (CFSH-1) (GenBank ID: OP351640) genes of E. sinensis were detected [40].…”
Section: Target-silencing Esfem-1c Gene In Juvenile and Mature Crabsmentioning
confidence: 99%